ANALISIS MACHINE LEARNING ALGORITMA REGRESI LINEAR UNTUK MEMPREDIKSI SAHAM DI BANK BRI DI BURSA SAHAM INDONESIA - Yenni Syahfutri Sipahutar; Ibnu Rasyid Munthe; Syaiful Zuhri Harahap (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Stocks are securities that have fluctuating characteristics. Therefore stock predictions are needed to determine stock prices in the future. The data used is actual data obtained from the Indonesian Stock Exchange. This study uses the CRISPDM model and uses the Linear Regression method in processing the data. Data processing is carried out using several techniques, namely manually (exel) and by application testing. The application used is Rapid Miner. And after testing, get the test results of a difference of 0 to 3%. And get a root mean square error (RMSE) value of 62.592. and based on the research, it was decided that the share price on January 4 2021 - December 9 2022 will experience stock price fluctuations in the future with a difference of 0 to 3% from the previous share price.